2012
DOI: 10.1186/1471-2350-13-62
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of common genetic variants in 82 candidate genes as risk factors for neural tube defects

Abstract: BackgroundNeural tube defects (NTDs) are common birth defects (~1 in 1000 pregnancies in the US and Europe) that have complex origins, including environmental and genetic factors. A low level of maternal folate is one well-established risk factor, with maternal periconceptional folic acid supplementation reducing the occurrence of NTD pregnancies by 50-70%. Gene variants in the folate metabolic pathway (e.g., MTHFR rs1801133 (677 C > T) and MTHFD1 rs2236225 (R653Q)) have been found to increase NTD risk. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 53 publications
1
72
0
3
Order By: Relevance
“…A pesar que nuestros resultados no encontraron asociación entre variantes del gen MTHFR y la EB, consideramos que la vía metabó-lica del folato no puede aún ser excluida del todo como una causa de MM después de la FAF en Chile. Existen variables en otros genes involucrados en esta vía, tales como TYMS, MTHFD1, SHMT1 y MFTC que han sido involucrados en la etiología de la EB en otras poblaciones 31,32 . Por lo tanto, se requiere de nuevos estudios con el fin de aclarar la contribución global de esta vía metabólica en nuestro país, idealmente con tamaños muestrales mayores que permitan detectar riesgos genotípicos menores.…”
Section: Discussionunclassified
“…A pesar que nuestros resultados no encontraron asociación entre variantes del gen MTHFR y la EB, consideramos que la vía metabó-lica del folato no puede aún ser excluida del todo como una causa de MM después de la FAF en Chile. Existen variables en otros genes involucrados en esta vía, tales como TYMS, MTHFD1, SHMT1 y MFTC que han sido involucrados en la etiología de la EB en otras poblaciones 31,32 . Por lo tanto, se requiere de nuevos estudios con el fin de aclarar la contribución global de esta vía metabólica en nuestro país, idealmente con tamaños muestrales mayores que permitan detectar riesgos genotípicos menores.…”
Section: Discussionunclassified
“…Inadequate folate status led to several types of birth defects, including certain heart defect, limb malformations, and in particular neural tube defects. Pangilinan et al (2012) reported common genetic variants in 82 candidate genes Pregnancy one-carbon metabolism and DNA methylation selected from 1-C-pathway, including MTHFR, as risk factors for neural tube defects. Other variants are involved in, for example, choline metabolism, reabsorption of vitamin B12, and mitochondrial folate transport.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most studies have shown that the MTHFR C677T genotype is related to biomarkers, such as serum folate, tHcy concentration, and folate intake. Other polymorphisms in the folate pathway have been found to be associated with a variety of complex traits and disorders including MTHFR A1298C, MTRR A66G, MTR A2756G, MTHFD1 G1958A, FOLH1 T484C, SLC19A1 A80G, and transcobalamin II ( TCN2 ) C776G, the transport protein of vitamin B12 (Weisberg et al 1998; Gaughan et al 2001; Laverdiere et al 2002; Kluijtmans et al 2003; Dervieux et al 2004; Martinelli et al 2006; Moskau et al 2007; Silva et al 2011; Pangilinan et al 2012; Xie et al 2012). Table 1 summarizes the distribution of serum tHcy, folate, vitamin B6, and vitamin B12 according to polymorphisms related to folate and tHcy metabolism (Hiraoka et al 2004; Hiraoka et al 2009).…”
Section: Genetic Polymorphisms Related To Folate and Thcy Metabolism mentioning
confidence: 99%